Introduction. Social Work in the D-A-CH Region - Hopmann, Benedikt; Schmitt, Caroline; Witte, Matthias D. (Pedagogika Społeczna Nova, 2023)
Article is describing development of social work in D-A-CH region (Germany, Austria and Switzerland), it growth and state of interest. It mention the ever-increasing social problems in Europe as well as some of possible solutions of mentioned ones. It underline overall social importance of social work and present some of national and international social work organizations.